Hidden Champions - Maren Harnack; Natalie Heger (Docomomo Journal, 2023)
Large-scale housing estates were the most significant and largest single investments implemented in many municipalities in the post-WWII period. They were emblematic of modern urban development until criticism of modern housing became widespread and reached Western Germany in the wake of the fundamental socio-critical movements shaking Europe around 1968. This criticism primarily reflected the voice of middle-class academics, who fed it into the media as well as into the architecture and planning discourse, which continues to dominate to these days. We will argue that this criticism stands in the way of recognizing large-scale housing estates as important testimonies of post-WWII history worthy of preservation. In times of tight housing markets, this criticism also enables significant alterations to the estates’ urban fabric as well as densification to generate additional homes without incurring land costs. As a result, we currently risk even the outstanding examples being altered beyond their ability to function as cultural monuments. This paper combines literature, archive material and extensive surveys of large-scale post-WWII housing estates in the Frankfurt Rhine-Main region to trace the changing perception of this housing type over time and its implications for the formal listing process. Whilst the current German legislation allows for the best specimens of large-scale post-WWII housing estates to be listed but factors outside the professional field prevents the authorities in charge from doing so. At the same time the benefits of listing would extend beyond the realm of building preservation to include better acceptance within the general public and improved identification for the residents. Two examples from the Rhine-Main Region will exemplify the challenges related to the preservation of large-scale housing estates.